Antibacterial Properties of Commercial Lavender Essential Oil against Some Gram-Positive and Gram-Negative Bacteria - Tkachenko, Halyna; Opryshko, Maryna; Gyrenko, Oleksandr; Maryniuk, Myroslava; Buyun, Lyudmyla; Kurhaluk, Natalia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2022)
Herbs and essential oils (EOs) have been used in medicine and veterinary, agriculture, the food industry, and cosmetology. Many EOs possess various biological properties, i.e. antibacterial, analgesic, anti-inflammatory properties, antioxidant, fungicide, larvicidal, antitumor activities, etc. Lavender oil is one of the most valuable aromatherapy oils. Its antibacterial and antifungal activities have been revealed in many studies. In the current study, the antibacterial properties of commercial lavender EO against some Gram-positive and Gram-negative bacteria were studied. To this intent, the antimicrobial susceptibility test was used (the Kirby–Bauer disk diffusion test for measuring zone diameters of bacterial growth inhibition). In the current study, Gram-negative strains such as Escherichia coli (Migula) Castellani and Chalmers (ATCC® 25922™), Escherichia coli (Migula) Castellani and Chalmers (ATCC® 35218™), Pseudomonas aeruginosa (Schroeter) Migula (ATCC® 27853™) and Gram-positive strains such as Staphylococcus aureus subsp. aureus Rosenbach (ATCC® 29213™), methicillin-resistant (MRSA), mecA positive Staphylococcus aureus (NCTC® 12493), Enterococcus faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC® 51299™) (resistant to vancomycin; sensitive to teicoplanin) and Enterococcus faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC® 29212™). Results of the current study revealed that resistant to the lavender EO were Gram-negative bacterial strains, such as E. coli (Migula) Castellani and Chalmers (ATCC® 25922™), E. coli (Migula) Castellani and Chalmers (ATCC® 35218™), P. aeruginosa (Schroeter) Migula (ATCC® 27853™) strains. The diameters of inhibition zones after the application of lavender EO were similar to control samples (96% ethanol). On the other hand, Gram-positive strains such as S. aureus subsp. aureus Rosenbach (ATCC® 29213™), methicillin-resistant S. aureus (NCTC® 12493), E. faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC® 51299™) and E. faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC® 29212™) were sensitive to lavender EO. The highest diameters of inhibition zones after the application of lavender EO were observed for E. faecalis strains. This study demonstrates the potential of commercial lavender essential oil as an antibacterial agent and for use in the treatment of MRSA infection. The data contributes to the ongoing scientific investigation regarding the application of essential oils as natural antibacterial agents.